What is the impact of tax avoidance on the value and reputation of multinational companies? - Ding, Gaohui (2022)
The issue of tax avoidance has long been a widespread phenomenon on a global scale. Tax avoidance is also generally recognised in numerous studies as an important corporate decision. This paper first examines the impact of tax avoidance by MNCs on the value of the firm. MNCs, as independent business entities, arrange tax avoidance activities in order to maximise the value of the company. The traditional view that tax avoidance reduces the tax burden and thus increases the value of equity also provides a theoretical basis for companies to implement tax avoidance. However, although tax avoidance gains tax savings for the company, it also increases the potential and unavoidable non-tax costs, which ultimately affect the value of the company. Secondly, this paper examines the relationship between tax avoidance and corporate reputation in MNCs. Corporate reputation is often considered to be an important constraint on tax avoidance by MNCs. Many scholars have also argued that the degree of corporate tax avoidance is negatively related to corporate reputation, but this hypothesis has not been tested using financial data. This paper finds no significant association between tax avoidance and corporate reputation based on empirical research. This suggests that tax avoidance activities do not cause damage to a company's reputation. This paper concludes that tax avoidance by MNCs is negatively correlated with firm value and is not correlated with firm reputation. The results of the study also provide implications for MNCs and tax authorities.